2022
DOI: 10.3390/biomedicines10071670
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammatory Cytokines in the Pathogenesis of Colorectal Carcinoma—Recent Findings and Review

Abstract: The inflammatory process plays a significant role in the development of colon cancer (CRC). Intestinal cytokine networks are critical mediators of tissue homeostasis and inflammation but also impact carcinogenesis at all stages of the disease. Recent studies suggest that inflammation is of greater importance in the serrated pathway than in the adenoma-carcinoma pathway. Interleukins have gained the most attention due to their potential role in CRC pathogenesis and promising results of clinical trials. Malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 245 publications
0
22
0
1
Order By: Relevance
“…Studies have shown that host immunity failed to produce a satisfactory antitumor immune response in most patients with CRC, which indicated that there is a mechanism of immune escape in CRC. 53 There are different subsets of T regulatory cells (Tregs), orchestrating critical roles in the regulation of antitumor immunity in CRC. Among them, forkhead box protein-3 ( + ) regulatory T cells (Foxp3+ Tregs) could regulate the antitumor immune response and inhibit the activity of cytotoxic T cells.…”
Section: Relationship Between Intestinal Immune Microenvironment and ...mentioning
confidence: 99%
“…Studies have shown that host immunity failed to produce a satisfactory antitumor immune response in most patients with CRC, which indicated that there is a mechanism of immune escape in CRC. 53 There are different subsets of T regulatory cells (Tregs), orchestrating critical roles in the regulation of antitumor immunity in CRC. Among them, forkhead box protein-3 ( + ) regulatory T cells (Foxp3+ Tregs) could regulate the antitumor immune response and inhibit the activity of cytotoxic T cells.…”
Section: Relationship Between Intestinal Immune Microenvironment and ...mentioning
confidence: 99%
“…Cytokines have been shown to play a key role in CRC stemness. It was reported that TME-derived factors with a pro-inflammatory action such as tumor necrosis factor-α (TNF-α) and interleukin (IL)-1β foster EMT phenotype and stem cell proliferation in human colon cancer cells[ 45 , 46 ]. Besides, it is known that CAFs, one of the most studied cells in the TME, produce IL-6, which promotes the expression of CCSC markers such as ALDH1 and LGR5[ 1 , 47 ].…”
Section: Influence Of the Tme On Ccsc Featuresmentioning
confidence: 99%
“…Inflammation, primarily chronic, and oxidative stress mediate different kinds of malignancies. Most of the studies on that correlation were collected from colon cancer patients who primarily have Crohn's disease (Monteleone et al, 2012;Klampfer L, 2011;Borowczak et al, 2022). Pro-inflammatory cytokines, such as IL-1β, IL-6 or TNF-α play a key role in proliferative diseases, and their overproduction may change the tumour microenvironment and stimulate tumour development.…”
Section: Introductionmentioning
confidence: 99%